Syntax By Abi Zaid Al-Ansari And Its Impact On Teaching The Arabic Language/ الإعراب لأبي زيد الأنصاري و أثره في تعليم اللغة العربية - Saeed Ali Alamri (Ijaz Arabi Journal of Arabic Learning, 2023)
Abu Zayd al-Ansari is one of the oldest and most reliable linguists, who transmitted and narrated it by hearing from the Arabs, and mentioned in his anecdotes strange words, which he was the source of, and exalted it and revered it, and a group of great imams participated in its explanation. Because of the importance of grammar in the Arabic language, many grammatical issues occurred in the book, which are considered assets of Arabic grammar, and something related to syntax occurred in it ,And the importance of expression in the science of grammar, and the fact that the expression is strongly adopted in understanding the meanings, and perhaps one movement changed the meaning to another meaning. The purposes of this research are 1. Test the extent of Abu Zayd's grammatical involvement 2. Was the Book of Anecdotes home to the usual grammatical dispute 3. Are there radical differences in the expression between grammarians. The methodology by collect those issues that related to the expression, and then analyze them. The results were summarized in 1. The importance of expression in understanding the meanings 2. Abu Zayd was like all grammarians 3 Commentators did not go too far into the exact characteristics of the expression4- They did not go outside the general framework of a linguistic book.